Eventful learning : learner emotions - Ritchie, Steve, 1953-; Tobin, Kenneth George, 1944- (Bold visions in educational research,, 2018)
"Eventful Learning: Learner Emotions provides cutting edge research on emotions and learning that are new and highly relevant to classroom researchers, teachers in pre-k-12 and college classrooms, and teacher educators. Event-oriented inquiry is appealing in that it emphasizes transformative potential of research while providing unique insights into everyday problems faced by teachers and teacher educators. The social and cultural theories used in the research blur disciplinary boundaries and support novel activities such as breathing meditation and cogenerative dialogue to provide students with greater autonomy and responsibility to regulate emotional intensity and enhance learning"--